‘White man’s disease’: American Indian AIDS conspiracy theories and the refusal of synthesis (Medicine Anthropology Theory, 2017)
Through critical reflection on the conspiracy theories told about the origins of HIV by American Indians, we learned that many community members refused the universalized aspects of AIDS prevention, education, and intervention. We found that standard HIV/AIDS-related prevention and treatment programs tend to universalize experiences with and responses to the AIDS epidemic and ignore – or push to the margin – alternative framings and understandings of this disease. Inspired by American Indians’ refusal to synthesize (in the Hegelian dialectical sense) their own experience into national and international AIDS knowledges, in this article we seek to engage with such marginal understandings, as well as their interactions with universal, individual, and community notions of care, AIDS, and health causality. The use of non-standard theories of the origins of AIDS by American Indians, we argue, disrupts the logic that attempts to universalize AIDS and community experiences. By making AIDS a ‘White Man’s disease’, Natives bring the epidemic in line with a history of social and health neglect by the settler state, and refuse to collapse their own, marginalized experiences and understandings of HIV/AIDS into dominant knowledges of the disease.